2019
DOI: 10.3390/antibiotics8040160
|View full text |Cite
|
Sign up to set email alerts
|

Do Global Regulators Hold the Key to Production of Bacterial Secondary Metabolites?

Abstract: The emergence of multiple antibiotic resistant bacteria has pushed the available pool of antibiotics to the brink. Bacterial secondary metabolites have long been a valuable resource in the development of antibiotics, and the genus Burkholderia has recently emerged as a source of novel compounds with antibacterial, antifungal, and anti-cancer activities. Genome mining has contributed to the identification of biosynthetic gene clusters, which encode enzymes that are responsible for synthesis of such secondary me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 103 publications
(172 reference statements)
0
6
0
1
Order By: Relevance
“…Secondary metabolite production is well characterized in B. thailandensis E264 [9a,e,16] . The majority of BGCs in this bacterium remain silent under most culture conditions [9,17] .…”
Section: Resultsmentioning
confidence: 99%
“…Secondary metabolite production is well characterized in B. thailandensis E264 [9a,e,16] . The majority of BGCs in this bacterium remain silent under most culture conditions [9,17] .…”
Section: Resultsmentioning
confidence: 99%
“…Some are produced by the modular non-ribosomal peptide synthetases (NRPS), whereas others are the product of NRPS-independent siderophore synthases ( Crosa and Walsh, 2002 ; Carroll and Moore, 2018 ). Biosynthetic gene clusters encoding proteins responsible for production and transport of secondary metabolites such as siderophores are often large, and the genes are subject to tight regulation ( Thapa and Grove, 2019 ). Such regulation may involve global transcriptional regulators, which generally regulate a large number of genes with distinct functionalities, and/or it may depend on local cluster-specific regulators, which are dedicated to a certain pathway.…”
Section: Siderophores Promote Bacterial Growth In a Host Environmentmentioning
confidence: 99%
“… The QS system, composed of BtaI2 and BtaR2, controls bactobolin production , and their encoding genes ( btaI2–btaR2 ) are located in the bactobolin operon (Figure ). Bactobolin was identified because of its antimicrobial activity against a broad range of bacteria including Bacillus subtilis , , Bacillus cereus , Chromobacterium violaceum , Staphylococcus aureus , and Escherichia coli and antifungal activity against Candida krusei. Bactobolin inhibits protein synthesis by binding to the 50S ribosomal subunit in proximity to the L2 protein. , Besides its antimicrobial effects, 1 was reported to have antitumor activity in vitro on different cell types , and in vivo in murine models. , A recent study demonstrated that the disruption of QS considerably altered the proteome of B. thailandensis E264, including the biosynthesis of bactobolin molecules, as well as various secondary metabolites such as 4-hydroxy-3-methyl-2-alkenylquinoline (HMAQ; 2 ) and its derivatives, whose production was considerably impacted …”
Section: Introductionmentioning
confidence: 99%